Escherichia coli Sequence Type 131 H30 Is the Main Driver of Emerging Extended-Spectrum-β-Lactamase-Producing E. coli at a Tertiary Care Center - James R. Johnson (American Society for Microbiology, 2016)
ABSTRACT The H30 strain of Escherichia coli sequence type 131 (ST131-H30) is a recently emerged, globally disseminated lineage associated with fluoroquinolone resistance and, via its H30Rx subclone, the CTX-M-15 extended-spectrum beta-lactamase (ESBL). Here, we studied the clonal background and resistance characteristics of 109 consecutive recent E. coli clinical isolates (2015) and 41 historical ESBL-producing E. coli blood isolates (2004 to 2011) from a public tertiary care center in California with a rising prevalence of ESBL-producing E. coli isolates. Among the 2015 isolates, ST131, which was represented mainly by ST131-H30, was the most common clonal lineage (23% overall). ST131-H30 accounted for 47% (8/17) of ESBL-producing, 47% (14/30) of fluoroquinolone-resistant, and 33% (11/33) of multidrug-resistant isolates. ST131-H30 also accounted for 53% (8/14) of dually fluoroquinolone-resistant, ESBL-producing isolates, with the remaining 47% comprised of diverse clonal groups that contributed a single isolate each. ST131-H30Rx, with CTX-M-15, was the major ESBL producer (6/8) among ST131-H30 isolates. ST131-H30 and H30Rx also dominated (46% and 37%, respectively) among the historical ESBL-producing isolates (2004 to 2011), without significant temporal shifts in relative prevalence. Thus, this medical center’s recently emerging ESBL-producing E. coli strains, although multiclonal, are dominated by ST131-H30 and H30Rx, which are the only clonally expanded fluoroquinolone-resistant, ESBL-producing lineages. Measures to rapidly and effectively detect, treat, and control these highly successful lineages are needed. IMPORTANCE The ever-rising prevalence of resistance to first-line antibiotics among clinical Escherichia coli isolates leads to worse clinical outcomes and higher health care costs, thereby creating a need to discover its basis so that effective interventions can be developed. We found that the H30 subset within E. coli sequence type 131 (ST131-H30) is currently, and has been since at least 2004, the main E. coli lineage contributing to key resistance phenotypes—including extended-spectrum-beta-lactamase (ESBL) production, fluoroquinolone resistance, multidrug resistance, and dual ESBL production-plus-fluoroquinolone resistance—at a United States tertiary care center with a rising prevalence of ESBL-producing E. coli isolates. This identifies ST131-H30 as a target for diagnostic tests and preventive measures designed to curb the emergence of multidrug-resistant E. coli isolates and/or to blunt its clinical impact.